The Challenges of Digital Justice in the Civil Courts - Ahmed Awed , Amal Fawzy (Journal of Legal Studies and Researches, 2020)
Despite of the advantages that are achieved by the use of electronic means in the patients, but there are concerns about the application of this system on my, some of them riveted on their usefulness and whether the application of these means of in to contribute to raising the efficiency of the case or that it will be at the expense of the safeguards for applicants and about the legality of what the procedures imposed in the proceedings, liabilities, civil, another aspect of specialty finishes to the future, and does that mean you completely abandon the human element and what was to become a computer is the norm depending on the modern techniques and consultation mechanisms that develop knowledge of Applied Mathematics.